Health Benefit Potentials Offered by Soy Isoflavones as a Consequence of the Various Phytochemical Properties: A Review - Rittisak, Sriwiang; Charoen, Ratchanee; Savedboworn, Wanticha; Detchewa, Pakkawat; Riansa-ngawong, Wiboon; Vittayaporn, Varaporn (Journal of Food Health and Bioenvironmental Science, 2023)
Bioactive soy isoflavones found in soybeans and other soy products offer antioxidant and anti-inflammatory properties and have been shown to present similar structural characteristics to 17-β-estradiol. Moreover, they have the ability to form bonds with estrogen receptors known as phytoestrogen. They are able to serve as the estrogen agonists of the relevant antagonists, depending on the estrogenic level of endocrine, although it is understood that isoflavones are involved in many complex processes based on their activity modes and compound structures. Isoflavones are now a matter of considerable interest to researchers due to their potential health benefits, especially in addressing the onset of cardiovascular disease, hormone-dependent cancers, type 2 diabetes, problems related to menopause, osteoporosis, and cognitive decline due to the aging process. This study provides an overview based on prior research of the various benefits that might be offered by soy isoflavones.